Evidence in cases regarding invalidity of marriage due to misjudgment of the spouse’s attribution (can. 1097 § 2 of the Canon Law ) pursuant to the case law of the Roman Rota - GÓRALSKI, WOJCIECH (Prawo Kanoniczne, 2012)
In cases regarding invalidity of marriage due to misjudgment of the spouse’s attribution, intended directly and substantially, similarly to cases under other invalidity titles, the key issue is the evidence. It is proving in a convincing way, that in a particular case all elements constituting a complete judicial figure provided in the second part of the second can. 1097 of the Canon Law can be verified. These elements are just the subject of evidence. A direct evidence (probatio directa) for the misjudgment comes from the statement of the party subject to misjudgment, acknowledged by reliable witnesses. An indirect evidence (probatio indirecta) is based on establishing how the party claiming to be subject to misjudgment (criterium aestimationis) has judged the other party’s attribution and what has been the reaction and way of conduct towards the spouse since no such an attribution was found in the spouse directly and substantially (criterium reactionis).